Cover, Content, and Editorial Note from Borneo J Pharm Vol. 3 No. 3 August 2020 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2020)
Alhamdulillahirabbil ‘Alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published in August 2020. Starting from this edition, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve the circulation of the best articles published by Borneo J Pharm. Also, starting from this edition, Borneo J Pharm applying the publish-as-you-go issue to present the title of the article that has been received as early as possible in order to increase the chances of readability and quotation of articles in Borneo J Pharm. This edition contains six articles consisting of Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Microbiology Pharmacy, Natural Product Development, and Clinical-Community Pharmacy. This edition includes writings from five countries including Indonesia, India, Libya, Nigeria, and the Russian Federation. The authors come from several institutions, including Sekolah Tinggi Ilmu Kesehatan Senior Medan, University of Tripoli, National Centre for Diabetes and Endocrinology of Libya, Pyatigorsk Medical and Pharmaceutical Institute, Kebbi State University of Science and Technology of Aliero, Federal Medical Centre of Birnin-Kebbi, Shri Gopichand College of Pharmacy, Meerut Institute of Engineering and Technology, NKBR College of Pharmacy and Research Centre, Universitas 17 Agustus 1945 Jakarta, and Universitas Esa Unggul. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the publication in the next edition in November 2020.